Single and double pass solar air heaters with wire mesh as packing bed - Aldabbagh, LBY; Egelioğlu, Fuat; İlkan, Mustafa (Pergamon, 2010)
The thermal performances of single and double pass solar air heaters with steel wire mesh layers are used instead of a flat absorber plate are investigated experimentally. The effects of mass flow rate of air on the outlet temperature and thermal efficiency were studied. The results indicate that the efficiency increases with increasing the mass flow rate for the range of the flow rate used in this work between 0.012 and 0.038 kg/s. For the same flow rate, the efficiency of the double pass is found to be higher than the single pass by 34–45%. Moreover, the maximum efficiencies obtained for the single and the double pass air collectors are 45.93 and 83.65% respectively for the mass flow rate of 0.038 kg/s. Comparison of the results of a packed bed collector with those of a conventional collector shows a substantial enhancement in the thermal efficiency.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.energy.2010.05.028) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Solar air heater; Thermal efficiency; Single and double pass solar air heater